Genome-wide identification and analysis of small RNAs originated from natural antisense transcripts in Oryza sativa - Zhou, Xuefeng; Sunkar, Ramanjulu; Jin, Hailing; Zhu, Jian-Kang; Zhang, Weixiong

(untitled) (Genome Research, 2009)
Natural antisense transcripts (NATs) have been shown to play important roles in post-transcriptional regulation through the RNA interference pathway. We have combined pyrophosphate-based high-throughput sequencing and computational analysis to identify and analyze, in genome scale, cis-NAT and trans-NAT small RNAs that are derived under normal conditions and in response to drought and salt stresses in the staple plant Oryza sativa. Computationally, we identified 344 cis-NATs and 7142 trans-NATs that are formed by protein-coding genes. From the deep sequencing data, we found 108 cis-NATs and 7141 trans-NATs that gave rise to small RNAs from their overlapping regions. Consistent with early findings, the majority of these 108 cis-NATs seem to be associated with specific conditions or developmental stages. Our analyses also revealed several interesting results. The overlapping regions of the cis-NATs and trans-NATs appear to be more enriched with small RNA loci than non-overlapping regions. The small RNAs generated from cis-NATs and trans-NATs have a length bias of 21 nt, even though their lengths spread over a large range. Furthermore, >40% of the small RNAs from cis-NATs and trans-NATs carry an A as their 5′-terminal nucleotides. A substantial portion of the transcripts are involved in both cis-NATs and trans-NATs, and many trans-NATs can form many-to-many relationships, indicating that NATs may form complex regulatory networks in O. sativa. This study is the first genome-wide investigation of NAT-derived small RNAs in O. sativa. It reveals the importance of NATs in biogenesis of small RNAs and broadens our understanding of the roles of NAT-derived small RNAs in gene regulation, particularly in response to environmental stimuli.